A toxin-binding alkaline phosphatase fragment synergizes Bt toxin Cry1Ac against susceptible and resistant Helicoverpa armigera. - Wenbo Chen (PLoS ONE, 2015)
Evolution of resistance by insects threatens the continued success of pest control using insecticidal crystal (Cry) proteins from the bacterium Bacillus thuringiensis (Bt) in sprays and transgenic plants. In this study, laboratory selection with Cry1Ac yielded five strains of cotton bollworm, Helicoverpa armigera, with resistance ratios at the median lethal concentration (LC50) of activated Cry1Ac ranging from 22 to 1700. Reduced activity and reduced transcription of an alkaline phosphatase protein that binds Cry1Ac was associated with resistance to Cry1Ac in the four most resistant strains. A Cry1Ac-binding fragment of alkaline phosphatase from H. armigera (HaALP1f) was not toxic by itself, but it increased mortality caused by Cry1Ac in a susceptible strain and in all five resistant strains. Although synergism of Bt toxins against susceptible insects by toxin-binding fragments of cadherin and aminopeptidase N has been reported previously, the results here provide the first evidence of synergism of a Bt toxin by a toxin-binding fragment of alkaline phosphatase. The results here also provide the first evidence of synergism of a Bt toxin by any toxin-binding peptide against resistant insects.